Jun in Drosophila development: redundant and nonredundant functions and regulation by two MAPK signal transduction pathways. - Kockel, L.; Zeitlinger, J.; Staszewski, L.M.; Mlodzik, M.; Bohmann, D. (Genes & Development, 1997)
Drosophila Jun is shown to be involved in different signal transduction pathways and developmental decisions. Dorsal closure, a morphogenetic process occurring during Drosophila embryogenesis, is regulated by Hemipterous (Hep) and Basket (Bsk), homologs of JNKK and JNK, respectively. Embryos lacking Jun activity exhibit a dorsal closure phenotype, very similar to that of bsk and hep mutants, indicating that Jun is a target of Hep/Bsk signaling. In eye and wing development Jun participates in a separate signaling pathway that is comprised of Ras, Raf, and the ERK-type kinase Rolled. In contrast to the strict requirement for Jun in dorsal closure, its role in the eye is redundant but can be uncovered by mutations in other signaling components. The redundant function of Jun in eye development may contribute to the precision of photoreceptor differentiation and ommatidial assembly.